Investigating Nuclear War Dangers under Spatial Grasp Paradigm - Sapaty, P.S. (Математичні машини і системи, 2019)
The paper describes applicability of the developed Spatial Grasp Technology (SGT) for describing patterns of international relations that can hint on probability of nuclear wars, while applying them worldwide in parallel and distributed mode. These recursive patterns in high-level language can be regularly launched and spatially matched from any world points, allowing us to investigate world security more efficiently than in a traditional centralised way. SGT is ideologically based on quite different, holistic, world vision directly as integral shapes and patterns rather than traditional parts-to-whole models. Its key element is high-level recursive Spatial Grasp Language (SGL) which can express distributed spaces and operations in them in a way understandable to both manned and unmanned components. У статті описується застосування розробленої технології просторового захоплення (ТПЗ) для відображення складних структур-шаблонів міжнародних відносин, які можуть вказувати на ймовірність світових ядерних воєн. Ці активні рекурсивні шаблони на мові високого рівня можуть регулярно запускатися і просторово зіставлятися з будь-яких точок світу, що дозволяє досліджувати міжнародну безпеку ефективніше, ніж за допомогою інших методів. ТПЗ ґрунтується на баченні світу безпосередньо у вигляді інтегральних форм і структур у противагу традиційним моделям від частин до цілого. Її ключовим елементом є рекурсивна мова просторового захоплення (МПЗ), яка відображує розподілені простори і активність у них у вигляді, зрозумілому як для пілотованих, так і безпілотних компонентів. В статье описывается применение разработанной технологии пространственного захвата (ТПЗ) для отображения сложных структур-шаблонов международных отношений, которые могут указывать на вероятность мировых ядерных войн. Эти рекурсивные шаблоны на языке высокого уровня могут регулярно запускаться и пространственно сопоставляться из любых точек мира, позволяя исследовать международную безопасность эффективнее, чем с помощью других подходов. ТПЗ основывается на видении мира непосредственно в виде интегральных форм и структур в противовес традиционным моделям от части к целому. Ее ключевым элементом является рекурсивный язык пространственного захвата (ЯПЗ), отображающий распределенные пространства и активность в них в виде, понятном как для пилотируемых, так и беспилотных компонентов.